Idit Sagiv, Representations of Animals on Greek and Roman Engraved Gems. Meanings and Interpretations - Amorai-Stark, Shua; Hershkovitz, Malka (Journal of Hellenistic Pottery and Material Culture, 2019)
Idit Sagiv’s 2018 monograph, a modified version of her 2015 PhD thesis, is a fine example of the scholarship we have come to expect from Archaeopress Academic Publishing on specialized archaeological classical subjects. It is a welcome book addition to the growing interest in the present field of classical glyptics, and all the more so because it discusses the vital sub-subject of animals in the field of glyptics throughout the Greco-Roman period as an important aspect of an ongoing developing culture. Many modern publications deal with the appearances, meanings and interpretations of specific groups of animals or with that of a single animal in Greek and Roman visual art or in texts throughout the ancient world or in a specific region. Some of them include also important discussions on depictions of animals in glyptics of both periods or in one period only. Yet, the subject of all major species of animals depicted in ancient engraved gems, while concentrating on their meaning, has rarely before been treated as a unified whole. S. discusses the glyptic depictions of all the major animal species (mammals, insects, etc.), underlines that of certain animals, mentions their manifestations in ancient sources and at the same time compares them to their depictions in various other ancient art media, attempting to identify the historical, cultural and religious concepts behind the themes depicted on the engraved gems.